Ascorbic acid-dependent gene expression in Streptococcus pneumoniae and the activator function of the transcriptional regulator UlaR2 - Afzal, Muhammad; Shafeeq, Sulman; Kuipers, Oscar P. (Frontiers in Microbiology, 2015)
In this study, we have explored the impact of ascorbic acid on the transcriptome of Streptococcus pneumoniae D39. The expression of several genes and operons, including the ula operon (which has been previously shown to be involved in ascorbic acid utilization), the AdcR regulon (which has been previously shown to be involved in zinc transport and virulence) and a PTS operon (which we denote here as ula2 operon) were altered in the presence of ascorbic acid. The ula2 operon consists of five genes, including the transcriptional activator ulaR2. Our β-galactosidase assay data and transcriptome comparison of the ulaR2 mutant with the wild-type demonstrated that the transcriptional activator UlaR2 in the presence of ascorbic acid activates the expression of the ula2 operon. We further predict a 16-bp regulatory site (5’-ATATTGTGCTCAAATA-3’) for UlaR2 binding in the Pula2. Furthermore, we have explored the effect of ascorbic acid on the expression of the AdcR regulon. Our ICP-MS analysis showed that addition of ascorbic acid to the medium causes zinc starvation in the cell that leads to the activation of the AdcR regulon.